An esterase-activatable prodrug formulated liposome strategy: potentiating the anticancer therapeutic efficacy and drug safety. Issue 3 (19th January 2022) - Shi, Linlin; Wu, Xinkai; Li, Tongyu; Wu, Yuan; Song, Liwei; Zhang, Wei; Yin, Luxi; Wu, Yuhui; Han, Weidong; Yang, Yunhai
Abstract : SN38 prodrug-based liposomal nanoassemblies achieved a markedly improved therapeutic efficacy and safety profile. The rational engineering of therapeutic nanomedicine is a promising approach for effective and safe drug delivery. Abstract : Liposomal nanomedicine represents a common and versatile carrier for the delivery of both lipophilic and hydrophilic drugs. However, the direct formulation of many chemotherapeutics into a liposomal system remains an enormous challenge. Using the topoisomerase I inhibitor 7-ethyl-10-hydroxycamptothecin (SN38) as a model drug, we combined lipophilic prodrug construction with subsequent integration into an exogenous liposomal scaffold to assemble a prodrug-formulated liposome for systemic administration. Reconstructing SN38 with lipid cholesterol via the esterase-activatable bond endows the resulting prodrug with elevated miscibility with liposomal compositions and esterase-responsive drug release in cancerous cells. The systemic administration of the prodrug-based nanoassemblies (Chol-SN38@LP ) exhibited preferential accumulation of therapeutic payloads in tumor lesions. Compared to the SN38 clinical counterpart irinotecan, our prodrug-based nanoassemblies with adaptive features showed elevated therapeutic efficacy (∼1.5 times increase of tumor inhibition) in a preclinical A549 lung carcinoma cell-derived mouse model and improved drug tolerability ( i.e., alleviated bloody diarrhea and liver damage) in multiple mice models. These results may be ascribed to extended systemic circulation and preferential tumor accumulation of our nanodrugs. Hence, our findings demonstrate that rational engineering of therapeutic nanomedicine is a promising approach for effective and safe delivery of antitumor chemotherapeutics, especially to rescue drug candidates that have failed in clinical trials owing to poor PK properties or severe toxicity in patients.